Key steps, insights and lessons learnt from establishing the Regional Hub for Fertilizer and Soil Health for West Africa and the Sahel - Trautman, Sabrina; Gosling, Amanda; Cramer, Laura K.; Zougmoré, Robert Bellarmin; Vanlauwe, Bernard; Crouch, Jonathan (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This learning note outlines the key steps, insights, and lessons learnt from the establishment of the Regional Hub for Fertilizer and Soil Health for West Africa and the Sahel (West Africa Regional Hub). It presents the political rationale and justification for the West Africa Regional Hub, highlighting critical events that shaped its development. Further, it details the process followed in formulating the Fertilizers and Soil Health Roadmap for West Africa and the Sahel, which was key to defining the West Africa Regional Hub’s mandate and core functions. The objective of this learning note is to provide guidance and support for the accelerated establishment of further fertilizer and soil health hubs in other African regions.